The Particle Size Distribution and Colour Profiles of Porang Powder with Variation Porang Flour Mass Feeds: A Preliminary Study: Profil Distribusi Ukuran Partikel dan Warna Bubuk Porang dengan Variasi Input Massa Tepung Porang: Studi Pendahuluan - Witoyo, Jatmiko Eko; Ni'maturohmah, Eva; Pamungkas, Bangkit Puji Putra; Permatasari, Nelsy Dian; Argo, Bambang Dwi; Yuwono, Sudarminto Setyo; Widjanarko, Simon Bambang (Universitas Brawijaya, 2025)
Porang is rich in glucomannan, making it valuable in food and non-food applications, often processed into porang flour. Size reduction of porang flour into porang powder is a crucial stage to meet the particle size standard of commercial konjac powder. However, this stage is rarely explored, especially when using a roller mill machine. This study aims to evaluate the performance of a batch roller mill machine on the particle size and colour of porang powder with various porang flour masses. The mass of porang flour used in this study was 100, 200, and 300 g, which were coded M100, M200, and M300, respectively, and the results obtained were analyzed descriptively. The particle size distribution was assessed using a particle size analyzer CILAS 1090-dry method, and colour was observed using the Colour Reader Minolta CR-10. The results showed that different mass variations of porang flour produced different particle size distribution patterns in the porang powder produced. Mathematically, the parameters d10, d50, d90, and the average diameter of porang powder follow an exponential equation as a function of the increasing porang flour mass, with R2 values ranging from 0.97 to 0.99. In addition, the average diameter of porang powder from treatment M100 was 68.81 µm and met the average particle size of commercial konjac powder. The colour L* and degree of whiteness (DoW) of porang powder decreased linearly as a function of the increasing porang flour mass, while the a* and b* values increased logarithmically, with R2 values more than 0.99.